Biotransformation of petroleum hydrocarbons and microbial communities in seawater with oil dispersions and copepod feces. Issue 2 (30th December 2015) - Størdal, Ingvild Fladvad; Olsen, Anders Johny; Jenssen, Bjørn Munro; Netzer, Roman; Altin, Dag; Brakstad, Odd Gunnar
Abstract: To determine biotransformation of components in crude oil dispersions in the presence of feces from marine copepods, dispersed oil was incubated alone, with the addition of clean or oil-containing feces. We hypothesized that the feces would contribute with nutrients to bacteria, and higher concentrations of oil-degrading bacteria, respectively. Presence of clean feces resulted in higher degradation of aromatic oil compounds, but lower degradation of n-alkanes. Presence of oil-containing feces resulted in higher degradation of n-alkanes. The effect of clean feces on aromatic compounds are suggested to be due to higher concentrations of nutrients in the seawater where aromatic degradation takes place, while the lower degradation of n-alkanes are suggested to be due to a preference by bacteria for feces over these compounds. Large aggregates were observed in oil dispersions with clean feces, which may cause sedimentation of un-weathered lipophilic oil compounds towards the seafloor if formed during oil spills. Highlights: Degradation of oil spills may be enhanced by the addition of inorganic nutrients. Copepod feces are high in nutrient and contain bacteria that can degrade oil. Oil dispersions were incubated with clean and oil-containing copepod feces. Biodegradation was high for dissolved oil compounds in the presence of clean feces. The indigenous feces bacteria were suggested to be capable of degradation of oil.